Strategi Penipuan Antarpribadi dalam Fenomena â€œTinder Swindlerâ€ pada Pengguna Aplikasi Online Dating Bumble - Saverius, Stephi; Palit, Stefanie Syalom Caroline; Aisyah, Adinda Nur; Hutabarat, Angel Rimbun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of technology has significantly impacted the way humans build romantic relationships, particularly in the context of seeking life partners. Previously, the process of finding a spouse was often limited to local social circles and face-to-face meetings. However, with the advent of the internet and innovations in the digital world, this process has undergone a profound transformation. Online dating applications have emerged as one of the products of this transformation, enabling individuals to meet and interact with people from various backgrounds and geographic locations. This study aims to analyze the phenomenon of â€œTinder Swindlerâ€ and the cases commonly encountered in online dating scams. The research method employed is qualitative description. Data acquisition methods include observation, interviews, and documentation. Primary data is obtained through direct interviews with informants, while secondary data involves information from social media and related articles. The results of the study indicate that one of the negative impacts of using online dating applications is the increase in cybercrime, such as fraud in online dating scams. This highlights the need for serious attention to these risks among users of online dating applications, as well as the importance of raising awareness of these risks and cultivating skills for wise and cautious digital interactions.